2016
DOI: 10.3766/jaaa.15060
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Noise Management Signal Processing Applying the American Academy of Audiology Pediatric Amplification Guideline: Verification Protocols

Abstract: Implications for clinical verification systems may be that greater standardization and the use of speech-in-noise test signals may improve the quality and consistency of noise reduction verification cross clinics. A suggested clinical protocol for verification of noise management in children's hearing aids is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Other participants suggested that background noise could be lowered relative to the signal of interest. This suggestion is consistent with current technologies as ANR systems are capable of lowering the background noise level without noticeable speech sound quality degradations (Bentler et al, 2008;Scollie et al, 2016). It is worth investigating the effect of ANR systems on music stimuli.…”
Section: Participants' Impressions Of Hearing Aidssupporting
confidence: 82%
“…Other participants suggested that background noise could be lowered relative to the signal of interest. This suggestion is consistent with current technologies as ANR systems are capable of lowering the background noise level without noticeable speech sound quality degradations (Bentler et al, 2008;Scollie et al, 2016). It is worth investigating the effect of ANR systems on music stimuli.…”
Section: Participants' Impressions Of Hearing Aidssupporting
confidence: 82%
“…The results of the current study indicate that the use of ANR and frequency-gain shaping do not improve or degrade speech recognition in noise. 2 9 11 12 20 It should be noted, however, that probe microphone verification confirmed that the ANR signal processing of the hearing aids used in this study did not attenuate gain in channels containing a positive speech-to-noise ratio. Also, probe microphone measurements confirmed that average-level (i.e., 65 dB SPL) and loud-level (i.e., 75 dB SPL) speech remained audible when frequency-gain shaping was provided for the purposes of noise management, so once again, a lack of a decrease in speech recognition in noise is not surprising.…”
Section: Discussionsupporting
confidence: 63%
“…Also, probe microphone measurements confirmed that average-level (i.e., 65 dB SPL) and loud-level (i.e., 75 dB SPL) speech remained audible when frequency-gain shaping was provided for the purposes of noise management, so once again, a lack of a decrease in speech recognition in noise is not surprising. Of note, Scollie et al 20 found large differences in the magnitude of gain reduction across several different hearing aids, so the findings of this study should not be globally applied to all contemporary hearing aids.…”
Section: Discussionmentioning
confidence: 75%
“…An item analysis may provide further insight about the performance of children with different levels of hearing loss within the various listening situations included in the PEACH as well as the impact of noise, as seen in other studies (e.g., Quar et al, 2013). This further work may help support clinicians' decisions about when to apply technologies to combat noise in the listening environment, for example (Scollie et al, 2016b).…”
Section: Discussionmentioning
confidence: 88%